1997
DOI: 10.1152/ajpheart.1997.273.4.h1699
|View full text |Cite
|
Sign up to set email alerts
|

Structural properties of rat mesenteric small arteries after 4-wk exposure to elevated or reduced blood flow

Abstract: We determined the structure of mesenteric small arteries after chronic elevation and chronic reduction of blood flow. In 6-wk-old rats, we ligated second-order side branches of every other first-order side branch of the superior mesenteric artery. This persistently reduced blood flow (−90%) in the vessels feeding into the ligated trees and elevated blood flow (+80%) in the nonligated mesenteric artery side branches. Four weeks after surgery, vessels that had been exposed to high blood flow (HF) or low blood fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
170
1
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(190 citation statements)
references
References 23 publications
17
170
1
1
Order By: Relevance
“…30 Similar observations were made by our group and others. 27,30,41,42 In the present study, we observed flowinduced outward hypertrophic remodeling but no hypotrophy in resistance arteries exposed to low blood flow in normotensive Wistar rats studied between 10 and 14 weeks of age. This indicates dependence of flow-related arterial remodeling on rat age 43 and strain.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…30 Similar observations were made by our group and others. 27,30,41,42 In the present study, we observed flowinduced outward hypertrophic remodeling but no hypotrophy in resistance arteries exposed to low blood flow in normotensive Wistar rats studied between 10 and 14 weeks of age. This indicates dependence of flow-related arterial remodeling on rat age 43 and strain.…”
Section: Discussionsupporting
confidence: 88%
“…This is in line with the flow-induced outward hypertrophic remodeling reported previously. 9,27,30,31 It was, however, not accompanied by alterations in arterial wall stiffness (Figure 2g), the elastin to collagen ratio or the macrophage count (Table 1). Surprisingly, after 7 weeks exposure to elevated blood flow, the outward remodeling (Figure 1b) and the increases in lumen diameter (Ø: to 455±21 mm, NS, Figure 2b), in medial mass (mCSA: to 14±1 Â 10 3 mm 2 , NS, Figure 2d) and the hyperplasia (# nuclei: to 41±3, NS; Figure 2f), were no longer statistically significant compared with control (NF) arteries of the same normotensive rats.…”
Section: Flow-related Arterial Remodeling In Normotensive Ratsmentioning
confidence: 94%
“…17,20,22,23 A reduction in blood flow induces a reduction in diameter, with or without arterial wall hypotrophy, decreased endothelium (NO)-dependent dilation and reduced contractility. 20,22,23,32,33,37 In addition to being a model that mimics the remodeling that occurs in hypoperfused tissues, LF remodeling has been shown to be equivalent to the eutrophic inward remodeling observed in several types of hypertension, such as endothelin-1-dependent hypertension and L-NAME-induced hypertension. 10 The main finding of this study is that the diameter reduction because of a decrease in blood flow in RAs was prevented by perindopril and candesartan, but not by hydralazine, suggesting selective involvement of angiotensin II and of its AT1R.…”
Section: Discussionmentioning
confidence: 99%
“…We also tested the role of superoxide anions and ERK1/2 in inward remodeling, as these molecules are involved in angiotensin II-mediated contraction in mesenteric RAs 18 as well as in cell migration. 19 We used a model previously described in rats 20,21 and mice, 22,23 which allows comparison of RAs submitted to low blood flow to adjacent arteries with normal flow (NF) in the same physiological conditions in vivo, without changes in hemodynamic conditions or hormonal environment. It should be noted that, in this model, flow decreases without changes in blood pressure or hemodynamic environment.…”
Section: Introductionmentioning
confidence: 99%
“…A pressure-diameter relationship was established by recording the lumen diameter while gradually increasing the distending pressure (20-120 mm Hg, 10 mm Hg steps). 23 After the experiment, vessels were fixed at 80 mm Hg in 4% phosphate buffered formaldehyde solution for 1 h at 37°C and stored in 70% ethanol.…”
Section: Arterial Pressure/diameter Relationshipsmentioning
confidence: 99%